(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract: This paper explores the food cultures of Tibet and Bhutan through the lens of women’s narratives, focusing on their roles in preserving and transforming culinary traditions. Drawing on personal stories, this study illustrates how women in these regions not only sustain but also adapt food practices to meet the demands of social and environmental changes. Through these narratives, food emerges as a symbol of cultural identity, resilience, and spiritual devotion, as well as a tool for community cohesion and heritage preservation.